Aktivitas Pelaksanaan Pekerjaan Pembagunan Gedung Di Pandemi Covid - Azza Arena; Rahayu Widiastuti (Politeknik Negeri Pontianak, 2022)
The purpose of the study was to examine factors that affected the activities of project workers before and during the pandemic. Data is obtained from individual perceptions on the implementation of building construction projects. The number of questionnaires depends on the needs of project activities, based on the experience and education of Bachelor of Engineering, Vocational High School, Junior High School, Elementary School with as many as 10 questionnaires each, so a total of 40 questionnaires and questionnaires can be 30 questionnaires.The results refer to the Likert scale with the choice of scores in this study quite a lot of influence (score 4), then continued by using three tests, first the percentage of worker activity factors, both Values t (Hypothesis) and r (Cholera moment), third Static values of Xbar control process and MR. The results of the study showed: (1) The percentage value before the pandemic, bachelor of engineering, vocational school, junior high school, elementary school above 50% of worker activity factors is very influential and when the pandemic is below 50% less influential, as well as beam work both before and during a pandemic; (2) Test scores t and r before the pandemic,bachelor of engineering, vocational school, junior high school, are very influential with high r values, only elementary school, no effect and r very low. When pandemic, bachelor of engineering, vocational school, very influential with a very high r-value and junior high, elementary school, has no effect with r very low; (3) The stability of work before the pandemic,bachelor of engineering, vocational school, junior high school, elementary school, has a lot of effects. When pandemic has no effect; (4) SPC MR before the pandemic,bachelor of engineering, vocational school, not in the thoroughness, out of bounds UCL is stable because it does not include an out of control pattern. Junior high school, elementary school, is not the thoroughness because the factor of workers being out of UCL limits and LCL being unstable means there is an uncontrolled process, but elementary school is stable because it does not include an out-of-control pattern. When a pandemic, bachelor of engineering, junior high school, the elementary school are in a thoroughness and work is stable because it does not include an out of control pattern; (5) SPC Xbar during a pandemic, bachelor of engineering, vocational school, junior high school, is not in the thoroughness because on the factor of workers out of UCL limits but stable because it does not include the pattern of out of control elementary school, in the accuracy,no work activity is out of bounds UCL or LCL. Unstable because it belongs to the 8 categories of Out of Control patterns, namely category no 4.